ANALISIS STRATEGI PEMASARAN BPRS BHAKTI SUMEKAR MELALUI DIGITAL MARKETING DALAM MENARIK MINAT NASABAH - Argantara, Zaid Raya; Khofifah, Indaratul (LAN TABUR : Jurnal Ekonomi Syariah, 2024)
Marketing is an activity that must be carried out by every economic activity, especially in every financial institution. because with these marketing activities, the goals of a company organization or institution can be achieved. And it is undeniable that the unavoidable changes in technological globalization require every company, institution and organization to be more sensitive to encourage one's creativity and innovation in the marketing process so as not to be left behind by the times. This study aims to analyze the digital marketing implemented by BPRS Bhakti Sumekar as a marketing strategy in attracting customers. The problem which arises in this research is about the strategy of BPRS Bhakti Sumekar marketing from digital marketing in attracting the interest of the customer and the impact of BPRS Bhakti Sumekar marketing from digital marketing to customer amount.This study uses a descriptive qualitative method with data sources used through interviews, observation and documentation. The analysis in this study was carried out in three stages, namely data reduction, data presentation, and data verification. According to the data analysis proposed by the theory of Miles and Huberman. The results of this study indicate that the marketing strategy carried out by BPRS Bhakti Semuker is through digital marketing by promoting shared social media such as Instagram, Facebook, websites, Videotron, and also Tiktok. BPRS Bhakti Sumekar's digital marketing has an impact on increasing the number of customers and the use of BBS Mobile facilities every year.